Keputusan Pembelian Ditinjau dari Word Of Mouth di PT Ebad Al Rahman Wisata Kabupaten Jember - Aprilya Fitriani; Amartyana Adiningsih (Politeknik Negeri Jember, 2023)
The limited quota and short time for the Hajj pilgrimage have resulted in quite long waiting lists. Many prospective regular Hajj pilgrims tend to choose other options, namely Hajj Plus or Umrah. The purchase decision of prospective Hajj Plus or Umrah pilgrims is influenced by several factors, one of which is word of mouth (WOM). This research uses a quantitative approach with a type of causality research. The sample was determined using an accidental sampling technique with a sample size of 100 respondents. The data analysis method uses simple linear regression. The research results show that word of mouth influences purchasing decisions. If pilgrims who have used Umrah and Hajj plus services increasingly provide recommendations through word of mouth, the confidence of prospective pilgrims in deciding to purchase Umrah and Hajj plus service products at PT Ebad Al Rahman Wisata Jember Regency will increase.